PENINGKATAN KECERDASAN DAN KREATIVITAS SISWA (Improving StudentsÃ¢â¬â¢ Intelligence and Creativity) PENINGKATAN KECERDASAN DAN KREATIVITAS SISWA (Improving StudentsÃ¢â¬â¢ Intelligence and Creativity) - Saparahayuningsih, Sri (KREATIF, 2010)
Improving studentsÃ¢â¬â¢ intelligence and creativity is very important for our countryÃ¢â¬â¢s development. It will be formed when educational process gives students opportunity to think convergently and divergently. So far, improving studentsÃ¢â¬â¢ intelligence and creativity has not been done satisfactorily. As a result, studentsÃ¢â¬â¢ intelligence and creativity cannot develop optimally. This writing offers the psycologists to optimize their activities so that studentsÃ¢â¬â¢ intelligence and creativity will be able to develop optimally. Teachers who can optimize studentsÃ¢â¬â¢ intelligence and creativity will be able to deliver students who can stand alone in the future. They will be positive value for their country. Keywords: intelligence, creativity, and education.